Towards a caring transdisciplinary research practice: navigating science, society and self. Issue 1 (1st January 2021) - Sellberg, My M.; Cockburn, Jessica; Holden, Petra B.; Lam, David P. M.
ABSTRACT: Transdisciplinary research that bridges science and society is needed to address the complex social-ecological sustainability challenges we are facing. However, many transdisciplinary researchers grapple with balancing the competing demands of scientific rigour and excellence, societal impact and engagement, and self-care. This is especially evident in the growing literature by early-career researchers describing the challenges of pursuing a transdisciplinary research career in social-ecological sustainability research. To guide discussion and reflection towards a flourishing transdisciplinary research practice, we synthesized our own and other researchers' experiences of using a transdisciplinary approach and formulated the heuristic of the 'Triple-S': caring for Science, Society and Self. This heuristic adds the frequently overlooked personal aspects of transdisciplinary research. Current dominant academic structures, cultures and metrics of success are not supporting a balanced and flourishing transdisciplinary research practice, but rather creating and exacerbating the trade-offs between these three aspects. As an example of a solutions-oriented approach, we developed a theory of change to address the changes we see are necessary to enable a transdisciplinary research practice in line with the Triple-S. We hope that this will foster academic environments where transdisciplinary research practice can flourish and the next generation of researchers are not burnt-out, but empowered.